Aesthetics and Islamic Education in Sasak Wayang: Integration of Religious Values and Local Culture - Asbullah Muslim; Abdul Haris; Mohammad Adnan; Abdul Haris Rasyidi; Sirajun Nasihin (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
These performances are not only viewed as entertainment, but also as an integral part of the rituals and traditions of the Sasak indigenous community in Kembang Kuning, East Lombok. This study aims to examine the role of Sasak Wayang, particularly the Menak Serandil play, in revitalizing moral education among the Sasak community. Using a descriptive qualitative approach, this study traces the history of Sasak Wayang, the revitalization strategies implemented, and their impact on strengthening the moral values of the community. Data collection was conducted through participatory observation during performances, in-depth interviews with puppeteers, performers, audience members, and community leaders, as well as analysis of relevant documents. The data was analyzed inductively through the stages of reduction, presentation, and conclusion drawing using a thematic approach. The results of the study show that Wayang performances in Kembang Kuning not only serve as cultural preservers, but also as an effective medium for building social solidarity, strengthening cultural identity, and conveying religious and moral messages that are relevant to the lives of the community. In particular, the Menak Serandil play is an important vehicle for conveying Islamic moral values such as courage, responsibility, and justice, while also reflecting the integration of the teachings of Imam al-Ghazali and Ibn Miskawaih in the context of moral education. Central figures such as Wong Agung Menak Jayengrana represent ideal figures in instilling the values of courage and devotion. Although this performance has not been integrated into the formal education curriculum, Wayang Sasak has proven to make a real contribution to the revitalization of moral education and character building in society. These findings reinforce the relevance of al-Ghazali's moral education theory regarding the importance of learning through real experiences, as well as Ibn Miskawaih's concept of character building through.